Effects of canrenone in patients with metabolic syndrome. (November 2013) - Derosa, Giuseppe; Bonaventura, Aldo; Bianchi, Lucio; Romano, Davide; D'Angelo, Angela; Fogari, Elena; Maffioli, Pamela
Abstract : Background: Metabolic syndrome is becoming a common disease due to a rise in obesity rates among adults. Objectives: The aim was to evaluate the effects of canrenone compared to placebo on metabolic and inflammatory parameters in patients affected by metabolic syndrome. A total of 145 patients were treated with placebo or canrenone, 50 mg/day, for 3 months and then 50 mg b.i.d. till the end of the study. Blood pressure, body weight, body mass index, fasting plasma glucose (FPG), fasting plasma insulin, HOMA-IR, lipid profile, plasma aldosterone, brain natriuretic peptide, high-sensitivity C-reactive protein (Hs-CRP), tumor necrosis factor-α (TNF-α) and M value were evaluated. Results: A decrease of blood pressure was observed in canrenone group compared to baseline; moreover, systolic blood pressure value recorded after 6 months of canrenone therapy was lower than the one recorded with placebo. Canrenone gave a significant decrease of FPI and HOMA index, and an increase of M value both compared to baseline and to placebo. Canrenone also decreased triglycerides and FPG was not observed with placebo. Canrenone also decreased plasma aldosterone, Hs-CRP and TNF-α compared to baseline and to placebo. Conclusion: Canrenone seems to be effective in reducing some factors involved in metabolic syndrome and in improving insulin-resistance and the inflammatory state observed in these patients.